Reformasi Hukum Keluarga Islam di Indonesia: Integrasi Maqāṣid al-Syarī‘ah dan Prinsip Keadilan di Era Digital - Ipansyah, Nor; Hafidzi, Anwar (IAIN BONE, 2025)
This study explores the reform of Islamic family law in Indonesia through the integration of maqāṣid al-sharī‘ah and the principles of justice and public welfare (maṣlaḥah) in response to the challenges of digital transformation. Employing a normative-juridical and comparative approach, it examines the limitations of the Kompilasi Hukum Islam (KHI) in addressing issues arising from technological developments and the growing demands for the protection of women and children. The findings reveal persistent inequalities in provisions concerning marriage guardianship, polygamy, and the legal status of children born out of wedlock. Guided by the objectives of maqāṣid al-sharī‘ah—particularly justice (‘adl), welfare (maṣlaḥah), and human dignity (karāmah insāniyyah)—the study affirms that authentic Islamic reform can be achieved without departing from Sharia’s normative foundations. Lessons from Morocco and Malaysia demonstrate that renewal within Islamic law is attainable through institutional innovation and contextual sensitivity. The research concludes that Indonesia’s Islamic family law reform should be maqāṣid-driven, justice-oriented, and digitally adaptive to ensure a fair, moral, and responsive legal framework consistent with the spirit of Islamic law in the modern age.